PENGARUH AROMATERAPI PAPPERMINT TERHADAP INTENSITAS MUAL MUNTAH PADA IBU HAMIL DENGAN HIPEREMESIS GRAVIDARUM DI RSUD EMBUNG FATIMAH KOTA BATAM TAHUN 2023 - Esin Esin; Siti Husaidah, Norma Jeepi (CV. Adiba Aisha Amira, 2024)
Excessive nausea and vomiting causes hyperemesis gravidarum which is a complication of nausea and vomiting in pregnancy. If this occurs continuously it can cause dehydration and an imbalance of electrolytes in the body with hypochloremic alcoholism. Peppermint aromatherapy is also known to be a safe and effective medicine for treating nausea and vomiting in pregnant women. The aim of this research was to determine the effect of peppermint aromatherapy on the intensity of nausea and vomiting in pregnant women with hyperemesis. This type of research uses Pre Experimental with a One Group Pretest Posttest Design. The research sample consisted of 15 pregnant women. The independent variable is peppermint aromatherapy and the dependent variable is nausea and vomiting. The instruments in this research are SOPs and observation sheets. The results of this study showed that before the intervention, mothers experienced severe nausea and vomiting (100%) and after the intervention, moderate nausea and vomiting (86.7%). Based on the test output of the paired sample T-test statistical test, a significance value of 0.000 was obtained, smaller than the 5% significance level (p-value = 0.000 < 0.05), so the conclusion is that Ha is accepted, which means there is an effect of peppermint aromatherapy on the intensity of nausea. Vomiting in Pregnant Women with Hyperemesis at Embung Fatimah Regional Hospital, Batam City in 2023.